The Role of UNICEF's Intervention Programs in Improving Polio Coverage During the Humanitarian Crisis in Yemen - Saleh, Hanan; Seidelson, Lucy Sebli (Human Resource Management Academic Research Society, 2021)
The poor humanitarian situation in Yemen resulted from many factors such as political instability, multiple localized conflicts and chronic underdevelopment. However, when the armed conflict started in March 2015 the whole country started experiencing a great shortage of vaccines which risks the lives of millions of children from infectious diseases such as polio. Therefore, fighting against polio was one of UNICEF’s battles in the country. This research aims to provide an assessment regarding the major interventions that UNICEF uses to deliver immunization services including polio vaccines to children during the current humanitarian crisis in the country. The analysis of the results showed that UNICEF’s support has a positive impact on children in Yemen. The coverage rate continues to improve slowly despite the challenges faced during the humanitarian crisis. Recommendations to resolve these challenges and to improve the current immunization interventions in the future were proposed. Keywords: Yemen, UNICEF, Humanitarian Interventions, Immunization, Polio